A Review on the Mechanical Performance of High-Volume Fly Ash Light-Weight Concrete - Abdulhussein F.K.; Beddu S.; Mohhamed D.B.; Al-Hubboubi S.; Abbas H. (Dr D. Pylarinos, 2025)
One of the most crucial ecological challenges is the removal of the ever increasing enormous quantities of Fly Ash (FA) generated from various industries and its reduction in landfill spaces. Light-Weight Aggregate Concrete (LWAC) is utilized in the construction industry as it can decrease the unit weight leading to lower dead load, thermos-insulation, and resistance against earthquakes. A number of researchers have implemented experimental programs on the use of large amounts of FA as a substitute for cement in various lightweight concrete mixtures. This study aims to present the recent efforts of adding attapulgite in LWAC and highlight its effects and the influence of its mixture with High Volume FA LightWeight Concrete (HVFALC) in terms of compressibility resistance, tensile strength, and rupture resistance. ? by the authors.